CLINICAL PROFILE OF CHILDREN PRESENTING WITH CONVULSIVE STATUS EPILEPTICUS AT A TERTIARY CARE HOSPITAL IN SOUTHERN INDIA - DINESH M NAYAK,; AJAY JHA,; CHANDRIKA D NAYAK, (International Journal of Pharma and Bio Sciences, 2016)
Convulsive status epilepticus (CSE) is a common pediatric neurological medical emergency associated with significant morbidity and mortality. The current study aimed to study the relation of age, sex, etiology and outcome in CSE. A total of 94 subjects aged 1month and above with CSE were included for the present study. Results were analyzed using Chi-Square test. Relation between age and CSE revealed that majority belonged to 1- 5 year age group. Majority of CSE were of the acute symptomatic category (37-50%). A duration of >12 hours of CSE was seen in acute symptomatic, progressive symptomatic and febrile group. Mortality was found to be less in all groups. Outcome in the acute symptomatic, febrile and idiopathic groups were good as compared to remote and progressive symptomatic groups. CSE had a male preponderance and majority belonged to 1-5 years and mortality was more in the acute symptomatic group.